2020
DOI: 10.1038/s41433-020-0898-9
|View full text |Cite|
|
Sign up to set email alerts
|

A 20-year audit of retinoblastoma treatment outcomes

Abstract: Objectives To evaluate the long-term treatment outcomes in intraocular retinoblastoma (RB) including the associated factors for eventual treatment with external beam radiotherapy (EBRT) and enucleation as well as to analyse the risk factors for metastasis and death in extraocular RB. Methods Retrospective analysis of 390 eyes from 256 (89.8%) intraocular RB and 29 (10.2%) extraocular RB cases diagnosed and treated between October 1998 and May 2018 at one of the largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
0
24
0
4
Order By: Relevance
“…The pooled estimate in 2010-20 was 6% (0-20, I²=98%) for LICs, 34% (21-49, I²=99%) for LMICs, 47% (38-56, I²=96%) for UMICs, and 70% (60-80, I²=96%) for HICs (table 2; appendix p 8). Globally, the pooled estimate improved significantly, from 22% [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] in 1980-89 to 44% [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] in 2010-20 (p=0•017).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled estimate in 2010-20 was 6% (0-20, I²=98%) for LICs, 34% (21-49, I²=99%) for LMICs, 47% (38-56, I²=96%) for UMICs, and 70% (60-80, I²=96%) for HICs (table 2; appendix p 8). Globally, the pooled estimate improved significantly, from 22% [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] in 1980-89 to 44% [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] in 2010-20 (p=0•017).…”
Section: Resultsmentioning
confidence: 99%
“…Although more studies with longer follow-ups are needed to be able to reach a conclusion, such fears have not, however, been confirmed to date. Indeed, when considering the studies reporting on metastatic disease, a similar metastasis rate of about 2% is found in children treated with systemic chemotherapy [ 15 , 16 , 19 , 22 , 25 , 26 ] or intra-arterial chemotherapy [ 23 , 29 , 33 , 34 , 35 , 37 , 38 , 42 ], whereas, according to a retrospective multicentric survey including more than 1100 patients managed with primary ( n = 464) or salvage intra-arterial chemotherapy ( n = 713) over a 10-year period, the risk of metastatic death from retinoblastoma has been estimated to be less than 1% [ 89 ].…”
Section: Resultsmentioning
confidence: 95%
“…Since the beginning of conservative retinoblastoma management, the main reason to stop eye-preserving therapies has always been, and still is related, independently of the treatment modalities used, to uncontrolled tumor activity (80–90% of SE) [ 2 , 4 , 5 , 6 , 7 , 10 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 29 , 30 , 31 , 32 , 34 , 35 , 37 , 38 , 40 , 41 , 53 , 54 , 55 , 56 ], while the occurrence of intraocular complications, especially those obscuring the fundus view, explains the remaining cases (10–20% of SE) [ 2 , 5 , 10 , 11 , 13 , 16 , 17 , 18 , 21 , 23 , 28 , 29 , 34 , 39 , 40 , 41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term survival rates of patients with metastatic RB remain unsatisfactory, mainly a result of invasion and metastasis (5). The frequency of metastatic RB ranges from 4.8 to 11% (6,7) and it remains major contributor to mortality and is associated with life-long poor prognosis (6,(8)(9)(10)(11). Frequent common sites of extraocular RB include the orbit, pre-auricular nodes, bones, central nervous system and liver, and each of these may influence the outcome of metastatic RB.…”
mentioning
confidence: 99%